Challenges to generate musical visualizations - Moura, Rute; Cabral, Giordano; Abreu, Jáder; Cunha, Mychelline; Almeida, Horhanna (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19437, 2021)
The technological acceleration of recent years has allowed for significant advances in data processing and the study of Music, an art with richly expressive and communicative information. In this article, we bring reports of experiences and contributions in the treatment of musical data extracted from digital MIDI and sound files, for the development of systems that generate musical visualizations.